La scolarisation des filles à Dakar au cours de la décennie 1990-2000 - Laure Moguérou (Cahiers de la Recherche sur l'Education et les Savoirs)
Documents about school policies in Senegal are formally inspired by the conclusions and recommendations of international and regional conferences considering girls’ schooling as a priority. But instead of encouraging equality, programs promoting girls’ schooling reasserted gender difference and complementarity between men and women roles. Urged to put their daughters to school, families are thinking roughly the same: schooling may help promoting women roles (being good spouses and good mothers) but cannot interfere with such destinies under any circumstances. Policy requirements were not strong enough to overturn the main determinant of girls underschooling, i.e. reluctance to durably change women’s status in the society.